Postoperative Pain Following Eye Enucleation: A Prospective Observational Study - Leister, Nicolas; Löser, Johannes; Gostian, Antoniu-Oreste; Gostian, Magdalena; Rokohl, Alexander C.; Fieber, Marc A.; Alkan, Deniz; Schumacher, Christine; Löw, Vanessa; Gordon, Erik; Böttiger, Bernd W.; Heindl, Ludwig M. (Medicina, 2024)
Background and Objectives: Enucleation of an eye is the most invasive procedure in ophthalmologic surgery. It can be the result of various diseases (malignant/chronic/trauma/infection) and is nevertheless relatively rare, but leads to the loss of a strongly innervated neuronal organ. This study systematically evaluates postoperative pain levels following enucleation of the eye globe. Materials and Methods: This prospective single-center study enrolled twenty-four patients undergoing enucleation of the eye globe. Perioperatively all patients completed (preoperative day, day of surgery, 1st, 2nd, and 3rd day following surgery) standardized questionnaires concerning their pain experience and treatment-related side-effects (internal protocol, QUIPS, painDETECT®). Patients received usual pain therapy in an unstandardized individual manner. Results: Preoperatively, mean average pain intensity of all included patients was 3.29 ± 2.46 (range, 0–8), 3.29 ± 3.24 (range, 0–8) on the day of surgery, 4.67 ± 1.90 (range, 2–10) on day 1, 3.25 ± 1.39 (range, 1–6) on day 2, and 2.71 ± 1.30 (range, 1–6) on day 3 after surgery. Mean maximum pain intensity was 4.71 ± 3.28 (range, 0–10) preoperatively, 4.04 ± 3.78 (range, 0–10) on the day of surgery, 5.75 ± 2.01 (range, 2–10) on day 1, 4.25 ± 1.89 (range, 2–10) on day 2, and 3.88 ± 1.54 (range, 2–8) on day 3 after surgery. Nineteen patients (79.2%) stated that they would have preferred more pain therapy. Conclusions: Patients undergoing eye enucleation report pain sensations in need of intervention in this university hospital. Thus, effective standardized pain treatment concepts are now a high priority to be established in an interdisciplinary manner containing standardized regimens and continuous regional procedures. Awareness of this problem in the medical team should be sharpened through targeted training and information.
CRIS-Team Scopus Importer:2024-05-03
Keywords: anophthalmic surgery; pain assessment; pain therapy; therapy side-effects